The Benefits of Backward Design in the English as a Foreign Language Context - Carlos Lenin Alvarez Llerena (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTThe Backward Design Model (BDM) is a curriculum approach in language teaching, which begins with the specification of learning outcomes that are the basis for developing instructional processes and input (Richards, 2013). This study aims to display a theoretical analysis of how the integration of the BDM has impacted English as a Foreign Language class. Thus, this study provides the results of reviewing research-based articles about how the integration of the BDM has benefited EFL teachers and students. These benefits are related to the main elements of the BDM, namely, designing learning to provide enduring understandings, assessing students’ performance based on acceptable evidence, and planning learning experiences and instructions based on desirable outcomes. The results indicated that the BDM indeed brought benefits to EFL teachers and students, revealing that this model's efficient application can help (a) teachers better understand the procedural knowledge of learning and (b) students improve their English language skills.ABSTRAKBackward Design Model merupakan pendekatan kurikulum dalam pengajaran bahasa yang diawali dengan spesifikasi hasil belajar yang menjadi dasar untuk pegembangan proses dan masukan pembelajaran (Richards, 2013). Penelitian ini bertujuan untuk menampilkan analisis teoritis tentang bagaimana integrasi Backward Design Model (BDM) berdampak pada kelas bahasa Inggris sebagai bahasa asing. Penelitian ini merupakan hasil dari telaah artikel berbasis penelitian tentang bagaimana integrasi BDM bermanfaat bagi para guru dan siswa EFL. Manfaat ini berkaitan dengan elemen utama BDM yaitu merancang pembelajaran untuk pemahaman yang bertahan lama, penilaian kinerja siswa berdasarkan bukti yang dapat diterima, dan merencanakan pengalaman dan instruksi pembelajaran berdasarkan hasil yang diinginkan. Hasil penelitian menunjukkan bahwa BDM memang membawa manfaat bagi para guru dan siswa. Hasil penelitian juga mengungkapkan bahwa penerapan model yang efisien ini membantu para guru untuk memiliki pemahaman yang lebih baik tentang pengetahuan prosedural pembelajaran dan juga membantu siswa untuk meningkatkan kemampuan berbahasa Inggris mereka.